Production of monoclonal antibodies against Streptococcus mutans antigens - Canettieri,Antonio Carlos Victor (2006)
Several studies have been conducted in the last decades aiming to obtain an anti-caries vaccine, however some studies have demonstrated cross reactivity between Streptococcus mutans surface antigens and the human cardiac tissue. In this work, the reactivity of five anti-Streptococcus mutans monoclonal antibodies (MoAb) (24A, 56G, C8, E8 and F6) was tested against oral streptococci, cardiac antigens and skeletal and cardiac myosins, aiming to evaluate the specificity of these MoAb. The hybrid producers of immunoglobulins of the IgG2b class were cloned by limit dilution and expanded in vivo. MoAb were tested by ELISA. The hybrid 24A reacted with S. mutans CCT 1910, S. salivarius CCT 0365 and S. pyogenes T23. No reactivity difference was observed among the tested species. Cross reactivity with heart and cardiac myosin was not confirmed and only reaction with myosin of skeletal muscle was observed (p = 0.0381). The hybrid 56G reacted with all the tested microorganisms and there was statistically significant difference between S. mutans and S. pyogenes T23 (p < 0.001). This hybrid also reacted with myosin of skeletal muscle (p = 0.0095). C8, E8 and F6 presented low reactivity against oral streptococci strains and no reactivity against cardiac antigens. The data of this study showed that the 24A and 56G anti-S. mutans MoAb presented reactivity with S. pyogenes and S. salivarius, reinforcing the occurrence of common antigens between these species. The tested MoAb presented low cross-reactivity with myosin of skeletal muscle, but anti-heart activity could not be confirmed.